S 2 Code for Sensitivity Analysis in Scilab - Oliviera, Roger (2024)
Scilab® (2023.1.0) codes were used for parameter sensitivity in the published kinetic models and in the integrated kinetic modeling of Acetone-Butanol-Ethanol Fermentation by Clostridium saccharoperbutilacetonicum N1-4 proposed in this study.